Usage of three-halfturn antenna at the Uragan-3M device - Lozin, A.V.; Moiseenko, V.E.; Grigor’eva, L.I.; Kozulya, M.M.; Krasyuk, A.Yu.; Kulaga, A.E.; Kramskoy, E.D.; Lyssoivan, A.I.; Maznichenko, S.M.; Mironov, Yu.K.; Pavlichenko, R.O.; Zamanov, N.V.; et al. (Вопросы атомной науки и техники, 2013)
Unshielded THT antenna is successfully used: (i) for heating of plasma prepared by the frame antenna pulse, (ii) for making an initial plasma with low density ~10¹⁰ cm⁻³ for further frame antenna operation, (iii) for independent generation and heating plasma at low magnetic fields B₀ <0.7 T and (iv) for mutual operation with frame antenna. In the last scenario both antennas contribute to plasma heating.